An Ngoni assessment of the role of ancestors within ancient Israelite world views and religion in Genesis 11:28-50:26 - Zulu, Edwin (Stellenbosch : Stellenbosch University, 2012)
Thesis (DTh)--Stellenbosch University, 1998.